Fungal interactions reduce carbon use efficiency. (4th July 2017) - Maynard, Daniel S.; Crowther, Thomas W.; Bradford, Mark A.
Abstract: The efficiency by which fungi decompose organic matter contributes to the amount of carbon that is retained in biomass vs. lost to the atmosphere as respiration. This carbon use efficiency (CUE) is affected by various abiotic conditions, including temperature and nutrient availability. Theoretically, the physiological costs of interspecific interactions should likewise alter CUE, yet the magnitude of these costs is untested. Here we conduct a microcosm experiment to quantify how interactions among wood‐decay basidiomycete fungi alter growth, respiration and CUE across a temperature and nitrogen gradient. We show that species interactions induced consistent declines in CUE, regardless of abiotic conditions. Multispecies communities exhibited reductions in CUE of up to 25% relative to individual CUE, with this biotic effect being greater than the observed variation attributable to abiotic conditions. Our results suggest that the extent to which fungal‐mediated carbon fluxes respond to environmental change may be influenced strongly by species interactions.